Can they stop the bleed? Evaluation of tourniquet application by individuals with varying levels of prior self-reported training. Issue 1 (January 2019) - McCarty, Justin C.; Caterson, Edward J.; Chaudhary, Muhammed A.; Herrera-Escobar, Juan P.; Hashmi, Zain G.; Goldberg, Scott A.; Goolsby, Craig; Lipsitz, Stuart; Haider, Adil H.; Goralnick, Eric
Highlights: Self-reported hemorrhage control training increases likelihood correct tourniquet application, but rate remains low at 1/3. Prior self-reported training is associated with increased willingness-to-assist and comfort level controlling hemorrhage. Willingness-to-assist and comfort level controlling bleeding are not associated with correct tourniquet application. Abstract: Background: Application of extremity tourniquets is a central tenet of multiple national initiatives to empower laypersons to provide hemorrhage control (HC). However, the efficacy of the general population who self-report prior first-aid (FA) or HC training on individual's ability to control bleeding with a tourniquet remains unknown. Therefore, the objective of this study was to assess the effectiveness of laypeople with self-reported prior FA or HC training to control bleeding with a tourniquet. Study Design: Employees of a stadium were assessed via simulation in their ability to apply a Combat Application Tourniquet. As a subgroup analysis of a larger study, participants who self-reported: 1) No prior training, 2) FA training only or 2) FA + HC training were compared. Logistic regression adjusting for age, gender, education, willingness-to-assist, and comfort level in HC was performed. Results: 317 participants were included. Compared to participants with no prior training (14.4%, n = 16/111), those with FA training only (25.2%, n = 35/139) had a 2.12-higher odds (95%CI:1.07-4.18) of correct tourniquet application while those with FA + HC (35.8%, n = 24/67) had a 3.50-higher odds (95%CI:1.59-7.72) of correct application. Participants with prior FA + HC were more willing-to-assist and comfortable performing HC than those without prior training (p < 0.05). However, reporting being very willing-to-assist [OR0.83, 95%CI:0.43-1.60] or very comfortable [OR1.11, 95%CI:0.55-2.25] was not associated with correct tourniquet application. Conclusion: Self-reported prior FA + HC training, while associated with increased likelihood to correctly apply a tourniquet, results in only 1/3 of individuals correctly performing the skill. As work continues in empowering and training laypeople to act as immediate responders, these findings highlight the importance of effective layperson education techniques.